Leucoridines A-D, cytotoxic strychnos-strychnos bisindole alkaloids from leuconotis - Kam, T.S.; Gan, C.Y.; Etoh, T.; Hayashi, M.; Komiyama, K. (American Chemical Society and American Society of Pharmacognosy, 2010)
Four new bisindole alkaloids of the Strychnos-Strychnos type, leucoridines A-D (1-4), were isolated from the stembark extract of Leuconotis griffithii. Alkaloids 1-4 showed moderate cytotoxicity against drug-sensitive and vincristineresistant human KB cells.